2012
DOI: 10.1177/1538574412450075
|View full text |Cite
|
Sign up to set email alerts
|

Deficiencies Persist in the Experience of UK Vascular Trainees

Abstract: Trainee experience is insufficient for a modern specialist practice. Separate specialty training in the United Kingdom must address these deficiencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…When asked about the percentage accounted for by the individual departments in terms of their training in interventional techniques, 38.5 % of respondents estimated that 75–100 % of their training had been obtained in the vascular surgical department, 30.8 % put this figure at 51–75 % and a further 30.8 % at 26–50 %. A UK survey of 217 trainee vascular surgeons, of which 153 (71 %) responded, painted a very different picture [ 19 ]. At the time of the survey 80 of these 153 (52 %) were working in posts that offered no endovascular training and 88 % (123/153) had performed less than 10 peripheral angiograms and/or angioplasties with or without supervision in the previous 12 months.…”
Section: Further Endovascular Trainingmentioning
confidence: 99%
“…When asked about the percentage accounted for by the individual departments in terms of their training in interventional techniques, 38.5 % of respondents estimated that 75–100 % of their training had been obtained in the vascular surgical department, 30.8 % put this figure at 51–75 % and a further 30.8 % at 26–50 %. A UK survey of 217 trainee vascular surgeons, of which 153 (71 %) responded, painted a very different picture [ 19 ]. At the time of the survey 80 of these 153 (52 %) were working in posts that offered no endovascular training and 88 % (123/153) had performed less than 10 peripheral angiograms and/or angioplasties with or without supervision in the previous 12 months.…”
Section: Further Endovascular Trainingmentioning
confidence: 99%
“…A similar type of study was repeated two years later, which showed no experience of EVLA, RFA or UGFS in 33%, 49% and 46% of trainees, respectively. 25 These are obviously major issues if endovenous treatments are to become first-line treatment with more time needing to be invested in the training of our vascular surgeons of the future.…”
Section: Training In Venous Surgerymentioning
confidence: 99%
“…Fellowships have been demonstrated to be beneficial to both trainee and training unit in multiple surgical specialities. [1][2][3][4] Trainees gain from experience beyond their base training units in far reaching aspects of their professional development beyond pure technical skills. Nontechnical skills including senior level decision making, case preparation and planning, managing a team and training more junior colleagues all contribute to the overall learning experience.…”
Section: Introductionmentioning
confidence: 99%